Sinais visuais determinantes da seleção de presas durante a captura de Aedes Aegypti (Diptera, Culicidae) pela aranha sinantrópica Menemerus bivittatus (araneae, salticidae): avaliação do efeito da forma, coloração e espaço tridimensional. - Lopes, Bruna Sara Alves (2022)
Although most spider species have a generalist diet, composed of a wide diversity of arthropods and even some plant items, the study of their potential for biological control of species that represent problems in crops and urban areas have been considered in recent years. Many species of the Salticidae family co-occur with species that are important vectors of diseases, such as mosquitoes, capable of transmitting and disseminating pathogens. It has already been demonstrated, for example, that an African species, Evarchaculicivora, has a preference for mosquitoes of the Anopheles genus and, among these, that there is still preferential predation of females that are carrying blood as a result of a recent feeding event.This preference proved to be innate and the selection of prey occurs based on chemical stimuli, but mainly visual. The objective of this research was to investigate which visual stimuli are used by a species of Salticidae, Menemerusbivittatus, which occurs in abundance in many Brazilian cities and which can act as an important mortality factor for the Aedes aegypti mosquito (Culicidae). Prey selection experiments were carried out in the laboratory, providing three types of models for the spiders: frozen mosquitoes with abdomens painted red and black, plastic models in the same colors with a spherical shape,and two-dimensional models in the shape of a mosquito, presented on a screen.The similarity between the frequencies of choice in the three experiments indicated that the visual component of a bloody abdomen and the red color of the spherical models should not be a determining factor in the selection of prey by Menemerusbivittatus. Although color perception is a common feature of the Salticidae visual system, wavelengths in the red spectrum are not universally perceptible by members of this family. It is possible that M. bivittatus (1) does not perceive the difference between the types of models used, and (2) that there is no preference for mosquitoes with a bloody abdomen. The first possibility is linked to the limitations of the chosen methods. As chemical cues can also be important in determining choices, it is possible that this perceptual component is essential in the case of M. bivittatus. The second possibility could arise from a low frequency of capturing blood-filled mosquitoes under natural conditions and/or from a relatively low nutritional advantage of capturing this item (which could be due to physiological particularities of the species or because mosquitoes may represent a part very small part of the diet of this species. The predator's potential impact on mosquito populations still depends on non-existent observations of its diet composition and further studies, including laboratory tests involving prey selection in a multi-option context and field predation observations.